Barriers and facilitators of shared decision making in acutely ill inpatients with schizophrenia—Qualitative findings from the intervention group of a randomised‐controlled trial. (13th July 2021) - Becher, Stefanie; Holzhüter, Fabian; Heres, Stephan; Hamann, Johannes
Abstract: Background: Shared decision making (SDM) is appreciated as a promising model of communication between clinicians and patients. However, in acute mental health settings, its implementation is still unsatisfactory. Objective: The aim of this study is to examine barriers and facilitators of SDM with acutely ill inpatients with schizophrenia. Design: A qualitative interview study was performed. Setting and Participants: The analysis is based on interviews with participants (patients and staff members) of the intervention group of the randomised‐controlled SDM PLUS trial that demonstrated a significant improvement of SDM measures for patients with schizophrenia on acute psychiatric wards. Main Variables Studied: Interviews addressed treatment decisions made during the current inpatient stay. The interviews were analysed using qualitative content analysis. Results: A total of 40 interviews were analysed and 131 treatment decisions were identified. According to the interviewees, SDM had taken place in 29% of the decisions, whereas 59% of the decisions were made without SDM. In 16%, a clear judgement could not be made. Barriers and facilitators of SDM were categorised into patient factors, clinician factors, setting factors and others. Clinicians mostly reported patient factors (e.g., symptoms) as barriers towards SDM, which were not mirrored on the patients' side. Facilitators included patient as well as clinician behaviour during consultations. Conclusion: Even in the context of a successful SDM intervention, the implementation of SDM for patients in the very acute stages of schizophrenia is often not possible. However, strong facilitators for SDM have also been identified, which should be used for further implementation of SDM. Patient or Public Contribution: During the development of the study protocol, meetings with user representatives were held.